Encyclopedia of Polymer Science and Technology 2003
DOI: 10.1002/0471440264.pst439
|View full text |Cite
|
Sign up to set email alerts
|

Metallocenes

Abstract: Ever since their discovery by Sinn and Kaminsky in 1979, the family of high activity homogeneous olefin polymerization catalysts known as “metallocenes” has been the subject of intense research and commercial development. While a structurally diverse group, metallocene catalysts are generally considered to have a few common features: a highly electrophilic, early transition metal or rare‐earth atom as the point of polymer chain attachment; a π‐bound cyclopentadienyl ring or isoelectronic analogue attached to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 232 publications
0
2
0
Order By: Relevance
“…Using methylaluminoxane (MAO) as the cocatalyst, a high Al/Zr‐ratio is needed for the solution process, the minimization of which is aspired for economical reasons. One possibility to realize this is to use heterogeneous catalysts20,21 with the metallocene being activated and, at the same time, immobilized on the surface of the carrier material which is impregnated with the cocatalyst. In the case of propene polymerization by metallocene catalysts, also the tacticity and the melting points are influenced 22–25…”
Section: Introductionmentioning
confidence: 99%
“…Using methylaluminoxane (MAO) as the cocatalyst, a high Al/Zr‐ratio is needed for the solution process, the minimization of which is aspired for economical reasons. One possibility to realize this is to use heterogeneous catalysts20,21 with the metallocene being activated and, at the same time, immobilized on the surface of the carrier material which is impregnated with the cocatalyst. In the case of propene polymerization by metallocene catalysts, also the tacticity and the melting points are influenced 22–25…”
Section: Introductionmentioning
confidence: 99%
“…Working in collaboration with long-time friends and colleagues, Malcolm and Jennifer Green, it was found that singly [Me 2 Si]-bridged ansa-niobocenes underwent intramolecular hydrogen exchange 3 orders of magnitude faster than unbridged analogs. 15 Little rate enhancement was observed upon introduction of a second [Me 2 Si] bridge. The origin of this effect was elucidated using DFT calculations, which suggested the electron population shifts from the ground state to the transition state most favorably for the singly bridged …”
Section: Metallocene-catalyzed Alkenementioning
confidence: 99%